THE ECONOMIC IMPORTANCE OF MIDDLE EAST OIL - Mostafa, Raouf (Dirasat in Economics and Business, 1967)
The following abstracts are short synopses of articles appearing in the Arabie half of the Review. They are summarized here for the benefit of those who cannot read Arable. In a like manner, each major English or French article is presented as A short résumé in the Arable section.